Machining of nickel-base, Inconel 718, alloy with ceramic tools under finishing conditions with various coolant supply pressures (2005)
Machining of Inconel 718 with whisker reinforced ceramic tool gave better performance in terms of tool life under high-pressure coolant supplies up to 15 MPa compared to conventional coolant supplies. The use of 15 MPa coolant supply pressure tend to suppress notching during machining thus improving tool life, while the use of higher coolant supply pressure of 20.3 MPa did not show improvement in tool life due probably to accelerated notch wear caused by water jet impingement erosion, Cutting forces decreased with increasing coolant supply pressure due to improved cooling and lubrication at the cutting interface as well as effective chip segmentation ensured by the momentum of the coolant jet. Surface roughness generated were well below the rejection criteria. This can be attributed to the round shape of the insert which tend to encourage smearing of the machined surface with minimum damage. Microstructure analysis of the machined surfaces show evidence of plastic deformation and hardening of the top layer up to 0.15 mm beneath the machined surface as a result of increase in dislocation density.